Esoteric teaching in the Stromateis of Clement of Alexandria - Itter, Andrew C. (Vigiliae Christianae, Supplements, 2009)
The Stromateis of Clement of Alexandria (c.150-215 CE) has received much scholarly debate over whether it can be accorded the role of the third and highest phase of his pedagogy. This was a treatise that promised an account of the true philosophy of Christ set down for Christians seeking higher knowledge of doctrine. This book takes a new approach to deciphering the nature and purpose of these enigmatic books concentrating on the close relationship between method and doctrine, and the number and sequence of the texts as they have come down to us. The outcome is a concise summary of current scholarship on Clement's method and a fresh picture of how he applies it to the transmission of esoteric doctrines.